2005
DOI: 10.1007/s10800-005-4726-5
|View full text |Cite
|
Sign up to set email alerts
|

The electrochemical and electrocatalytic behaviour of glassy metals

Abstract: The suitability of a selection of amorphous alloys as electrocatalysts or as inhibitors for hydrogen evolution (HE) was investigated in 1 M KOH at 25°C. Mild basic conditions were chosen so as to make direct comparison with other data, where available. The alloys studied were the known glassy alloys Fe 67 Co 18 B 14 Si 1 , Co 66 Fe 4 Si 16 B 12 Mo 2 , Fe 40 Ni 40 B 20 and Fe 40 Ni 40 P 14 B 6 and an entirely new glassy alloy Zr 73.22 Ti 19.71 Cu 1.24 Fe 5.83 . The electrochemical techniques of slow sweep anodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…[81,82] An early work by Enyo et al in 1983 highlighted this method and the resulting enhancement for the hydrogen evolution reaction. [81,82] An early work by Enyo et al in 1983 highlighted this method and the resulting enhancement for the hydrogen evolution reaction.…”
Section: Surface Treatment and Activation For Mgn Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…[81,82] An early work by Enyo et al in 1983 highlighted this method and the resulting enhancement for the hydrogen evolution reaction. [81,82] An early work by Enyo et al in 1983 highlighted this method and the resulting enhancement for the hydrogen evolution reaction.…”
Section: Surface Treatment and Activation For Mgn Fabricationmentioning
confidence: 99%
“…[81,82] An early work by Enyo et al in 1983 highlighted this method and the resulting enhancement for the hydrogen evolution reaction. Following this work, several other authors have reported similar findings [40,81,[84][85][86] and the activation treatments grew to the use of other chemicals and to electrochemical methods soon becoming a common practice. Following this work, several other authors have reported similar findings [40,81,[84][85][86] and the activation treatments grew to the use of other chemicals and to electrochemical methods soon becoming a common practice.…”
Section: Surface Treatment and Activation For Mgn Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic studies [128] on the hydrogenation of carbon monoxide by Fe-based alloy indicated that the activity is augmented by a treatment in HNO 3 solution. Guczi et al [129] thought that the surface composition and valence state determined in depth were related to the catalytic activity and selectivity revealed in CO + H 2 reaction. An increased number of nickel and iron sites by removing of the prevailing boron oxide, iron oxide, and iron oxide layer after HCl treatment was responsible for the enhanced catalytic activity, as shown in Figure 15, that is, the activity of the FeB sample in as-received state was about twice that observed for the FeNiB sample, on the other hand, comparing the HCl etched samples, the activity of the FeNiB alloy was about 30 times higher than that of the FeB ribbon.…”
Section: Electrocatalytic Properties Of Metallic Glassesmentioning
confidence: 99%
“…Since the first report of Fe-based metallic glass as a catalytic material in 1981 [1], a number of investigations have been focused on the synthesis of Fe-based metallic glasses for catalytic applications, such as ammonia synthesis [2], acetylene hydrogenation [3], CO hydrogenation [4][5][6] and hydrogenation [7]. On the other hand, the metallic glasses also showed good electrocatalytic activities, and the activities were further improved by the pretreatment in an acid solution such as HF, HCl or HNO 3 [8][9][10]. The improved electrocatalytic properties were attributed to changes in the surface compositions and/or surface area by the pretreatment.…”
Section: Introductionmentioning
confidence: 99%